Rumination and Empathy on Forgiveness in College Students Who Have Been Victims of Dating Violence - Fani, Devitha Meutia (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Dating violence often leaves anger or hurt on the part of the victim. For individuals who have experienced this condition, forgiveness is important so that they can move into the future with lighter feelings. The condition of always remembering painful events (rumination) and a willingness to empathize with the perpetrator is predicted to influence the victim to forgive the perpetrator. The objective of this research is to investigate the impact of rumination and empathy on forgiveness in college students who have been victims of dating violence. The respondents of this study were 74 college students who had been victims of violence in dating, which were obtained using purposive sampling technique. The measuring instrument used in this research is the scale of Transgression-Related Interpersonal Motivation Inventory (TRIM-18), Rumination of Interpersonal Offence (RIO), and Empathic Understanding. The method of data analysis used in this study is multiple regression technique. The results of the analysis show that together rumination and empathy have a very significant effect on forgiveness in respondents who are college students who have been victims of dating violence, with a large effect of 17.7%. By comparing each variable, it is known that rumination has a very significant effect and the effect of empathy is significant. So even though the two variables influence respondents to be able to forgive the perpetrator, it is rumination that is more influential. This means that the more often you remember the painful events that have been experienced, the more difficult it is for the respondent to forgive the perpetrator.Kekerasan dalam pacaran seringkali meninggalkan kemarahan atau sakit hati di pihak korban. Bagi individu yang pernah mengalami kondisi tersebut, memaafkan menjadi hal penting agar dapat melangkah ke masa depan dengan perasaan lebih ringan. Kondisi selalu mengingat peristiwa menyakitkan (ruminasi) dan kemauan untuk empati terhadap pelaku, diprediksi mempengaruhi korban untuk memaafkan pelaku. Penelitian ini bertujuan untuk menguji pengaruh ruminasi dan empati terhadap pemaafan pada mahasiswa yang pernah menjadi korban kekerasan dalam berpacaran. Responden penelitian ini merupakan 74 mahasiswa yang pernah menjadi korban kekerasan dalam berpacaran, yang diperoleh dengan menggunakan teknik purposive sampling. Alat ukur yang digunakan dalam penelitian ini adalah yaitu skala Transgression-Related Interpersonal Motivation Inventory (TRIM-18), Rumination of Interpersonal Offence (RIO), dan Empathic Understanding. Teknik analisis data yang digunakan adalah teknik regresi berganda. Hasil analisis menunjukkan bahwa secara bersama-sama ruminasi dan empati memberikan pengaruh yang sangat signifikan terhadap pemaafan pada responden yang merupakan mahasiswa yang pernah menjadi korban kekerasan dalam pacaran, dengan besar pengaruh sebanyak 17,7%. Dengan membandingkan masing-masing variabel diketahui bahwa ruminasi memberikan pengaruh yang sangat signifikan dan pengaruh empati adalah siginifikan. Jadi walaupun kedua variabel mempengaruhi responden untuk bisa memaafkan pelaku, namun ruminasi yang lebih berpengaruh. Hal ini berarti bahwa semakin sering mengingat-ingat peristiwa menyakitkan yang pernah dialami, semakin menjadikan responden lebih sulit untuk bisa memaafkan pelaku.